Projecting Distribution of the Overwintering Population of Sogatella furcifera (Hemiptera: Delphacidae), in Yunnan, China With Analysis on Key Influencing Climatic Factors. Issue 1 (22nd October 2015) - Hu, Shao-Ji; Liu, Xiao-Fei; Fu, Da-Ying; Huang, Wei; Wang, Xue-Ying; Liu, Xiao-Jun; Lü, Jian-Ping; Ye, Hui
Abstract : Sogatella furcifera (Horváth) is the most threatening migratory rice pest in Yunnan, China. S. furcifera overwinters in low- altitude basins and valleys in southern Yunnan and migrates northward in spring and summer of the following year, causing serious damage during migration. The overwintering distribution, areas, and spatial pattern of S. furcifera are relevant to the migration and outbreak of this pest. Based on a 4-yr field survey (2010–2013), this study projected areas suitable for S. furcifera to overwinter using a species distribution model, and analyzed the key influencing climatic factors using principal component analysis (PCA) and ecological niche factor analysis (ENFA). Our field survey showed that the northern latitudinal- and upper elevation limits of overwintering S. furcifera was 25.4° N and 1, 608 m in western Yunnan and 24.2° N and 1, 563 m in eastern Yunnan. The species distribution model produced a fragmented distribution pattern, with most of which in western Yunnan and only a few in eastern Yunnan. The PCA and ENFA analyses showed that the mean temperature of the driest quarter and the precipitation of the coldest quarter significantly influenced the distribution of S. furcifera in winter. The results suggested that the complex topography, spatial differences in winter temperatures, and host availability altogether determined the distribution of overwintering S. furcifera . Compared with previous surveys, the northern latitudinal- and upper elevation limits of overwintering S. furcifera were higher, while the population became rarer in some suitable areas due to change of farmland utilization in winter and possibly climate change.